2013
DOI: 10.4103/0019-557x.119819
|View full text |Cite
|
Sign up to set email alerts
|

Association of child feeding practices with nutritional status of under-two slum dwelling children: A community-based study from West Bengal, India

Abstract: A cross-sectional study was conducted among 245 under-two slum-dwelling children in Bankura town, West Bengal, to assess their feeding practices and its association with nutritional status. Child's gender, number of family members, standard of living (SLI), and household food security (HFS) were assessed through interview of mothers/ caregivers. Child feeding practices were measured with Composite Child Feeding Index comprising of age-appropriate, multiple, infant and young child feeding (IYCF) indicators and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 0 publications
3
37
0
1
Order By: Relevance
“…Therefore, for the past decade, health educations have been provided house to house by the community health workers for the people in the rural area but not for the urban people. In general, our finding is consistent with other observational studies that calculated the percentage of children that had minimum dietary diversity in other developing countries, such as India (24.4%) (Khanal et al 2013), Nepal (30.4%) (Mukhopadhyay et al 2013) and Bangladesh (42%) (Kabir et al 2012). Although this illustrates that dietary diversity is a big concern in Ethiopia and other developing countries, it is a big improvement considering the result of a study conducted in 2010 in Ethiopia where only 5% of the children met the minimum dietary diversity (Central Statistical Agency 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, for the past decade, health educations have been provided house to house by the community health workers for the people in the rural area but not for the urban people. In general, our finding is consistent with other observational studies that calculated the percentage of children that had minimum dietary diversity in other developing countries, such as India (24.4%) (Khanal et al 2013), Nepal (30.4%) (Mukhopadhyay et al 2013) and Bangladesh (42%) (Kabir et al 2012). Although this illustrates that dietary diversity is a big concern in Ethiopia and other developing countries, it is a big improvement considering the result of a study conducted in 2010 in Ethiopia where only 5% of the children met the minimum dietary diversity (Central Statistical Agency 2011).…”
Section: Discussionsupporting
confidence: 92%
“…This indicated that the composite of feeding practices improve the nutritional status of children. This finding is similar with the study done in West Bengal, India, the finding on that study was Per unit increase in standardized IYCF score, under nutrition by all three indicators was likely to be reduced by 2-3% and the association was significant after adjustment for the potential confounders [27]. The finding of this study contradicts the findings of a study in urban settings of Ethiopia [28]where the composite index was unable to show an impact on nutritional status in the multivariate model.…”
Section: Pulverized Mangifera Indica (Mango) Seed Kernel Mitigated Mosupporting
confidence: 90%
“…Delhi (33,43,47,57,58,70,81,87,100,105) Madhya (69,106) Mangalore (80,102) Haryana (75,86) Rajasthan (52) Gujarat (28,64) Kashmir (38) Ludhiana (53) Himachal (82) Uttarakhand (48,61,77) Uttar Pradesh (36,60,71,98,103) Assam (41,104) Bihar (55,83) West Bengal (30,56,84) Odisha (Orissa) (76,78) Andhra Pradesh (42,74) Maharashtra (27,35,39,50,(66)(67)(68)101) Karnataka (44,(45...…”
Section: Dietary Diversitymentioning
confidence: 99%
“…Meal frequency was explored in twenty-one studies (26,27,30,31,33,34,(36)(37)(38)(39)42,46,50,51,(55)(56)(57)(58)(59)(60)(61) . In ten studies, MMF was attained by between 25 and 50 % of the study population (27,31,33,37,38,46,(57)(58)(59)61) .…”
Section: Meal Frequencymentioning
confidence: 99%